'It's concerning', but is it your concern? Objectivity, advocacy and activism in gambling research. Issue 1 (2nd January 2021) - Delfabbro, Paul; King, Daniel L.
ABSTRACT: In recent years, there has been an increase in advocacy and social media activism in the field of gambling studies. Much of the focus of this activity has been directed toward concern about the lack of concerted government action to reduce gambling-harm as well as concern about industry influence in government policy and research agendas. It is thought that such activity could be successful in reducing harmful behavior as has been witnessed in relation to smoking in previous decades. In this paper, we highlight some concerns about this advocacy activity as it applies to gambling. We support the view that careful scrutiny should be applied to any research directly funded for industry due to the potential conflict of interest. However, we believe that: (a) greater scrutiny should be given to the role of government and other interest groups in the determination of research agendas and (b) greater transparency be displayed by public health advocates who are strongly opposed to gambling on moral, ethical or theoretical grounds. We discuss the potential pitfalls of conflating research academic and advocacy roles and the threats which this can pose for balanced, inclusive and objective debates in the field of gambling studies.